Modeling NASA swarm-based systems: using agent-oriented software engineering and formal methods - Peña, Joaquin; Rouff, Christopher A.; Hinchey, Mike; Ruiz-Cortés, Antonio (Software and systems modeling, 2011)
The need to collect new data and perform new science is causing the complexity of NASA missions to continually increase. This complexity needs to be controlled via new technological advancements and balanced with a reduction in mission and operation costs. Planned and hypothesized missions involve self-management, biological-inspiration based on swarms, and autonomous operation as a means of achieving these goals. We consider a tailored software engineering approach to developing such systems based on agent-oriented software engineering and formal methods. We report on advances in modeling, implementing, and testing NASA swarm-based concept missions.